Peran Spesialisasi Industri Auditor dalam Memoderasi Pengaruh Audit Tenure dan Ukuran KAP terhadap Audit Report Lag - Misnawati; Nindito, Marsellisa; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2024)
This study aims to determine the role of auditor industry specialization in directing the impact of audit tenure and size of Public Accounting Firm on audit report lag. Sampling was carried out with the aim of purposive sampling. Panel data regression analysis was used to test the hypothesis, and the sample size included 30 energy sector companies listed on the Indonesia Stock Exchange between 2021 and 2023 with outlier data. Based on the findings of this study, audit report lag is significantly affected by auditor industry specialization and tenure, but not by the size of the Public Accounting Firm. While auditor industry specialization does not moderate the effect of Public Accounting Firm size on audit report lag, it does moderate the effect of audit tenure on audit report lag.